2018
DOI: 10.1111/nyas.13583
|View full text |Cite
|
Sign up to set email alerts
|

Western lifestyle and immunopathology of multiple sclerosis

Abstract: There is increasing evidence for a sudden and unprecedented rise in the incidence of multiple sclerosis (MS) in Westernized countries over the past decades, emphasizing the role of environmental factors. Among many candidates, rapid changes in dietary habits seem to play a role in the pathogenesis of MS. Here, we summarize and discuss the available evidence for the role of dietary nutrients, such as table salt, fatty acids, and flavonoids, in the development and pathogenesis of MS. We also discuss new and emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 188 publications
(358 reference statements)
0
24
0
Order By: Relevance
“…Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative demyelinating disease of the central nervous system defined by a wide range of symptoms and signs that disrupt physical, cognitive, emotional, and social functioning.MS affects 2.6 women for every man with the condition [7,8], while it has been estimated that at least 2.3 million individuals worldwide suffer from the disease [9]. MS is among the most common causes of neurological disability in young adults [10,9]. The exact aetiology or causes of the disease still remains unknown, however, various traditional and non-traditional factors have been proposed as contributors such as genetic, environmental and immunological [11,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative demyelinating disease of the central nervous system defined by a wide range of symptoms and signs that disrupt physical, cognitive, emotional, and social functioning.MS affects 2.6 women for every man with the condition [7,8], while it has been estimated that at least 2.3 million individuals worldwide suffer from the disease [9]. MS is among the most common causes of neurological disability in young adults [10,9]. The exact aetiology or causes of the disease still remains unknown, however, various traditional and non-traditional factors have been proposed as contributors such as genetic, environmental and immunological [11,10].…”
Section: Introductionmentioning
confidence: 99%
“…MS is among the most common causes of neurological disability in young adults [10,9]. The exact aetiology or causes of the disease still remains unknown, however, various traditional and non-traditional factors have been proposed as contributors such as genetic, environmental and immunological [11,10]. What is more evident is the pathophysiology of MS which is characterized by chronic inflammation, disruption of the blood-brain barrier and immune cell infiltration into the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are a family of phenolic substances sharing the same backbone structure of 2-pheny1-1,4-benzopyronemay, which are very abundant in nature, being accumulated in regular human diets including flowers ( Zhang and Ma, 2018 ), fruits ( Chang et al, 2018 ), vegetables, tea, wine ( Matveeva et al, 2018 ), and so on ( Szmitko and Verma, 2005 ). With the basic core scaffold, flavonoids have been demonstrated to exhibit relevant biological properties involving strong activity for anti-oxidant ( Pietta, 2000 ), anti-allergy ( Kawai et al, 2007 ; Castell et al, 2014 ), anti-inflammatory ( Nijveldt et al, 2001 ; Serafini et al, 2010 ; Matias et al, 2014 ), anti-microbial ( Cushnie and Lamb, 2005 ), and anti-obesity ( Hughes et al, 2008 ) effects.…”
Section: Introductionmentioning
confidence: 99%
“…These results should be taken in context of the predominantly plant-based diet of the study subject, as previous reports found western, high-fat, low-fiber diet promoted dysbiosis and neuroinflammation in MS (43), while plant-based high-fiber diets decreased MS risks (44). However, prior to the study, while on the high-fiber diet, the subject's symptoms remained troublesome and led to the decision to test FMT.…”
Section: Discussionmentioning
confidence: 64%